Discovering inhibitors of TEAD palmitate binding pocket through virtual screening and molecular dynamics simulation. (June 2022) - Li, Yimin; Li, Yaqi; Ning, Chao; Yue, Jianda; Zhang, Cheng; He, Xiao; Wang, Ying; Liu, Zhonghua
Abstract: Transcriptional enhanced associate domain (TEAD) proteins bind to YAP/TAZ and mediate YAP/TAZ-induced gene expression. TEADs are not only the key transcription factors and final effector of the Hippo signaling pathway, but also the proteins that regulate cell proliferation and apoptosis. Disorders of Hippo signaling pathway occur in liver cancer, breast cancer, colon cancer and other cancers. S-palmitylation can stabilize the structure of TEADs and is also a necessary condition for the binding of TEADs to YAP/TAZ. The absence of TEAD palmitoylation prevents TEADs from binding to chromatin, thereby inhibiting the transcription and expression of downstream target genes in the Hippo pathway through a dominant-negative mechanism. Therefore, disrupting the S-palmitylation of TEADs has become an attractive and very feasible method in cancer treatment. The palmitate binding pockets of TEADs are conservative, and the crystal structures of TEAD2-palmitoylation inhibitor complexes and the potential TEAD2 inhibitors are more than other TEADs, TEAD2 can be selected to be the target receptor. In this study, structure-based and ligand-based virtual screening, molecular dynamics simulations, Molecular Mechanics Poisson-Boltzmann Surface Area (MM/PBSA) calculations, residue decomposition binding energy calculations, and ADME predictions have been performed to discover 11 potential TEAD2 S-palmitylation inhibitors. ChEBML196567 and ZINC000013942794 are the most recommended, because they formed strong binding energies and stable hydrogen bonds with TEAD2 and have good drugbility and high human oral absorption. We found that it was easier to find the targeting small molecules using a combination of structure-based and ligand-based virtual screening methods. Besides, a new core structure has been found in the selected small molecules. In addition, we analyzed the binding modes of these small molecules to TEAD2, and confirmed the hot spot residues Cys380, Ser345, Tyr426, Phe428, Ile408, and Met379. Availability of data and material: Supplementary materials are available online. Graphical Abstract: ga1 Highlights: Pan-inhibitors for transcriptional enhanced associate domain (TEAD). 11 potential inhibitors with new skeleton for TEAD palmitate binding pocket. Potential drug candidates for cancer treatment related to Hippo pathway. Combination of structure-based and ligand-based virtual screening, binding energy calculations and ADME predictions.